Pengaruh Model Pembelajaran Daring Akibat Pandemi Covid-19 Terhadap Prestasi Belajar Mahasiswa UNAI pada Semester Genap 2019/2020 - Albinur Limbong (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2020)
This article is a report of a study regarding the impact of a drastic change in learning model from face to face in class to become virtual class, due to covid-19 pandemic, in Universitas Advent Indonesia in academic year 2019/2020. The population for this study is all students enrolled both in the odd and even semester 2019/2020, i.e. 1516 students, and all population become sample. The academic achievement is seen solely by Semester Grade Point Average (GPA) achieved by the students in end of semester. Generally, at the university level, the academic achievement increased, although there are two faculties, i.e. Economics and Education, the academic achievement of students decreased slightly, while for other faculties, the achievement increased. Based on the batch, the first year student showed a negative impact of daring system, while other batches performed positively. In terms gender, both male and female students have a positive impact of daring learning system, however female students performed better than male students. These results are surprising, since it was assumed before that the academic achievement will be decreased due to the drastic change in the learning model from class room model to virtual model. This study implied that the covid-19 pandemic brought a positive impact in the academic achievement of UNAI students. This happened since both faculties and students of UNAI were successful to overcome any difficulties or challenges in the learning model due to the covid-19 pandemic However, this study needs to be continued to see the long term observation, whether the positive impact still happens or not in the odd semester 2020/2021.